Pengembangan Pendidikan Vokasi Perspektif Maqāṣid al-Syar’ah dalam Mewujudkan Sumber Daya Manusia yang Produktif Maslahah - Moch Mahsun; Kasuwi Saiban; Misbahul Munir (Bidayatuna, 2022)
In particular, human development is subject to the search for fulfillment through an educational process based on Maqāṣid al-Syar'ah. The point of Maqāṣid al-Syar'ah is to protect mankind and protect them from harm in this world and the hereafter from each individual. This research is aqualitative research through a literature review review with descriptive analysis. This study results that the practice of 6 important things in Maqâshid al-syarî'ah is expected to be the main reference in implementing life practices,especially from the fields of spirituality, education, economics and health. This is used as a form of balancing integrated Islamic and general knowledge, this research only focuses on the preparation of human resources in terms of education